2020
DOI: 10.15766/mep_2374-8265.10988
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Refugee Health Care Delivery in the Community Setting: An Educational Workshop for Multidisciplinary Family-Centered Care During Resettlement

Abstract: Introduction: With 70.8 million people displaced worldwide, there is an increasing need for medical professionals to provide medical care to refugees. Insufficient training on refugee health poses a barrier to effective care delivery. Methods: This workshop addressed common challenges in providing family-centered pediatric refugee care in community settings as well as barriers related to policy changes. Presentations covered prearrival experiences, medical screening, and trauma-based care. In small groups, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…7,10 In a review of the literature, we identified four published refugee health curricula for medical students and pediatric residents. [10][11][12][13] Methods used in these curricula included simulated patient cases, case-based discussion in small groups, lecture sessions with guest speakers, and in-person clinical experiences at a refugee clinic. [10][11][12][13] Surveys completed by participants in these curricula emphasized participants' engagement with and enjoyment of the material despite little formal training in refugee health through the standard health professions curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,10 In a review of the literature, we identified four published refugee health curricula for medical students and pediatric residents. [10][11][12][13] Methods used in these curricula included simulated patient cases, case-based discussion in small groups, lecture sessions with guest speakers, and in-person clinical experiences at a refugee clinic. [10][11][12][13] Surveys completed by participants in these curricula emphasized participants' engagement with and enjoyment of the material despite little formal training in refugee health through the standard health professions curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Methods used in these curricula included simulated patient cases, case-based discussion in small groups, lecture sessions with guest speakers, and in-person clinical experiences at a refugee clinic. [10][11][12][13] Surveys completed by participants in these curricula emphasized participants' engagement with and enjoyment of the material despite little formal training in refugee health through the standard health professions curriculum. [10][11][12][13] Little is known about the impact of using direct health education interactions between refugees and residents to enhance resident education in this area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] However, few graduate medical education programs provide training in practices and techniques that prepare residents to assume future roles as physician advocates for a more equitable health care system, 3,4 and few of these curricula have been published. When we reviewed curricula designed to teach advocacy skills to address health inequities in the US health care system and published in MedEdPORTAL, [7][8][9][10][11][12][13] we found that none addressed leadership development or featured community organizing, none targeted learners at the start of residency training, and few were crossinstitutional.…”
Section: Introductionmentioning
confidence: 99%
“…McHenry and colleagues published a study evaluating the effectiveness of a brief intervention on caring for Burmese patients directed at resident physicians. 19 A review of MedEdPORTAL revealed several publications specific to refugee health, among them resources providing direction on both pediatric 20 and adult refugee health. 21 To date, no current curriculum focuses on the specific needs of Burmese refugees.…”
Section: Introductionmentioning
confidence: 99%